Directions for Harmonizing Foreign Trade Regulation Legislation with WTO Requirements - Jumaboyev , Ixtiyor (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article analyzes the issues of harmonizing the foreign trade regulation legislation of the Republic of Uzbekistan with the requirements of the World Trade Organization. In particular, it examines directions for improving customs tariff policy, non-tariff restrictions, technical regulation, and sanitary and phytosanitary measures.